The Direct Damaging Effect of Some Agricultural Chemicals Used Locally in Iraq on the DNA of Escherichia coli - Jawad, Mohammed M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Agricultural chemicals on a large scale of use throughout the world, and there are many studies about these chemicals and its disadvantages, but most of them were limited to its impact on mammals such as rodents in determine. This study was designed to determine the impact of these chemicals on DNA damage for E. coli bacteria from Iraq. The DNA is similar in terms of structure and function in all living organisms with a different in number and sequence of the nitrogenous bases among living organisms. This study showed that snails and slugs killer material Metaldehyde are strongly bind with the DNA extracted from bacteria, and herbicides Glyphosate also showed that clearly when treated with DNA extracted from bacteria, as well as with the plasmid DNA.